The Nexus between Carbon Emissions and Per Capita Income of Households: Evidence from Japanese Prefectures - Kayani, Umar Nawaz; Fahlevi, Mochammad; Mumtaz, Roohi; Qaruty, Reema Al; Asad, Muzaffar (International Journal of Energy Economics and Policy, 2023)
Household consumption is significantly influenced by various factors. Despite this, the intricate nature of consumption behaviors and the lack of comprehensive data from the supply chain have led to an incomplete recognition of the attributes contributing to home emissions at the city level. Through the analysis of city-level household consumption in relation to energy demand, utilizing a city-scale input-output model and urban residential consumption inventories, this study considers the environmental responsibility inherent in residential consumption for Japanese’s Prefectures, this study reveals that variations in this responsibility based on household type and season. The study period is 2013-2022. Various factors are taken into account when examining emissions by age and month, including emission type, source, fuel variety, and consumption items. These assertions stem from emissions data computed using the system boundary method. Our hypothesis is supported by a range of statistical findings, encompassing summary statistics and regression analysis. The connection between residential emissions and GDP is also explored through regression analysis. We uncover evidence indicating that carbon emissions in Japan fluctuate with the seasons and across diverse categories. These statistics illustrate a notable discrepancy in the regional distribution of carbon emissions, owing to evident variations in consumption rates and patterns.